2022
DOI: 10.18332/tid/149227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between the level of addiction and exhaled carbon monoxide levels with neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in smokers

Abstract: INTRODUCTION Smoking has been reported to increase systemic inflammation. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are used as markers for systemic inflammation. In this study, the primary aim was to determine the NLR and PLR ratios in smokers. Secondly, we aimed to evaluate the relationship between the level of addiction and carbon monoxide (CO) level in the expiratory air, with these ratios. METHODS This study was designed as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Samplers: National Institute for Occupational Safety and Health (NIOSH) bioaerosol sampler (BC251) with SKC AirChek XR5000 pump (SKC, Eighty Four, PA, USA) Sampling rates and time: 3.5 L/min for 30 min, and 6-13 air samplers per week. Sampling periods: October 2016 to June 2018 except during the summer holidays in 2017 (weeks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Children who attend daycare centers are exposed to higher levels of infectious agents and air pollutants-including carbon monoxide (CO), carbon dioxide (CO 2 ), and ultrafine particles (UFPs)-than those who are cared for at home [12,13]. Studies have reported that children exposed to UFPs (aerodynamic diameter < 0.1 µm) have an increased risk of respiratory infection and hospital admission [14,15], and the amount of influenza virus found in the fraction of UFP S less than 0.25 um was 15% [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samplers: National Institute for Occupational Safety and Health (NIOSH) bioaerosol sampler (BC251) with SKC AirChek XR5000 pump (SKC, Eighty Four, PA, USA) Sampling rates and time: 3.5 L/min for 30 min, and 6-13 air samplers per week. Sampling periods: October 2016 to June 2018 except during the summer holidays in 2017 (weeks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Children who attend daycare centers are exposed to higher levels of infectious agents and air pollutants-including carbon monoxide (CO), carbon dioxide (CO 2 ), and ultrafine particles (UFPs)-than those who are cared for at home [12,13]. Studies have reported that children exposed to UFPs (aerodynamic diameter < 0.1 µm) have an increased risk of respiratory infection and hospital admission [14,15], and the amount of influenza virus found in the fraction of UFP S less than 0.25 um was 15% [16].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Porto revealed that the concentrations of CO 2 in nurseries and kindergartens were 1563 and 1492 ppm, respectively [ 20 ]. Scholars have also considered CO as an indicator of respiratory inflammation [ 21 , 22 , 23 , 24 ]. Specifically, studies have reported that patients with upper or lower respiratory tract infections and current smokers had increased concentrations of exhaled CO [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation